KEAP1/NRF2 as a druggable target - Dinkova-Kostova, Albena (Archives of Pharmacy, 2023)
Nuclear factor erythroid 2-related factor 2 (NRF2; encoded by NFE2L2) is an inducible transcription factor that regulates the expression of a large network of genes encoding proteins with cytoprotective functions. NRF2 also has a role in the maintenance of mitochondrial and protein homeostasis, and its activation allows adaptation to numerous types of cellular stress. NRF2 is principally regulated at the protein stability level by three main ubiquitin ligase systems, of which the regulation by Kelch-like ECH-associated protein 1 (KEAP1), a substrate adaptor protein for Cul3/Rbx1-based ubiquitin ligase, is best understood. KEAP1 is a multi-functional protein and, in addition to being a substrate adaptor, it is a sensor for electrophiles and oxidants. Pharmacological inactivation of KEAP1 has protective effects in animal models of human disease, and KEAP1 is now widely recognized as a drug target, particularly for chronic diseases, where oxidative stress and inflammation underlie pathogenesis. Many compounds that target KEAP1 have been developed, including electrophiles that bind covalently to cysteine sensors in KEAP1, non-electrophilic protein-protein interaction inhibitors that bind to the Kelch domain of KEAP1, disrupting its interaction with NRF2, and most recently, heterobifunctional proteolysis-targeting chimeras (PROTACs) that promote the proteasomal degradation of KEAP1. The drug development of KEAP1-targeting compounds has led to the entry of two compounds, dimethyl fumarate (BG-12, Tecfidera®) and RTA-408 (omaveloxolone, SKYCLARYS®), in clinical practice. In 2013, dimethyl fumarate was licenced as the first oral first-line therapy for relapsing-remitting multiple sclerosis and is also used for the treatment of moderate-to-severe plaque psoriasis. In February 2023, omaveloxolone was approved by the United States Food and Drug Administration as the first and only drug for patients with Friedreich’s ataxia.
Keywords: Electrophile; KEAP1; NQO1; NRF2; omaveloxolone; sulforaphane